Efficacy and safety of tyrosine kinase inhibitors (dasatinib, nilotinib) in the treatment of chronic phase chronic myeloid leukemia - E. G. Lomaia; E. G. Romanova; E. I. Sbityakova; A. Yu. Zaritskiy (Онкогематология)
Current treatment options for chronic myeloid leukemia (CML) with imatinib allowed achieving long-term progression-free and overall survival and improved patient quality of life. In cases of imatinib resistance therapy with second-generation tyrosine kinases inhibitors – dasatinib and nilotinib – is also possible. The article represents a literature review evaluating efficacy and toxicity of both drugs and highlighting some of the practical issues of CML treatment after first-line therapy failure.